Evaluation of the Efficacy of Ultrasound-Guided Visualized Acupotomy Combined with Rehabilitation Training in Treatment of Knee Osteoarthritis - PAN Xigui; LIAN Xiaowen; FU Jiehui; ZHANG Zesheng; LIU Xuemei; XIU Zhongbiao (康复学报)
ObjectiveTo observe the effect of ultrasound-guided visualized acupotomy combined with rehabilitation training for knee osteoarthritis.MethodsA total of 70 patients with knee osteoarthritis, admitted to the Affiliated Rehabilitation of Fujian University of Traditional Chinese Medicine from August 2021 to March 2023 were selected. According to the random number table method, they were divided into ultrasonic needle knife group and conventional treatment group, with 35 cases in each group. Four patients in the ultrasound needle knife group and 6 patients in the conventional treatment group withdrew. Ultimately, 31 patients were included in the ultrasonic needle knife group and 29 in the conventional treatment group. The ultrasonic needle knife group underwent needle knife treatment under ultrasound guidance, combined with quadriceps rehabilitation training. The conventional treatment group underwent general acupuncture treatment plus quadriceps rehabilitation training. The visual analogue scale (VAS), the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores, peak torque values of the quadriceps femoris (PT), and efficacy and safety before and after treatment were compared.ResultsAfter treatment, the VAS scores decreased in both groups, with the ultrasound needle knife group showing a more significant decrease compared with the conventional treatment group (P<0.05). WOMAC scores decreased in both groups after treatment, and the WOMAC scores of the ultrasound needle knife group were lower than those of the conventional treatment group (P<0.001). The PT of the quadriceps increased significantly in both groups after treatment, and there was more significant in the ultrasound needle knife group compared with the conventional treatment group (P<0.001). On the basis of the selection of regular meridian disease points according to meridian sinew theory, the top 4 frequently selected points were "Binneixia" 87.10% (27/31), "Hedingci" 83.87% (26/31), "Yinlingshang" 77.42% (24/31), and "Binwaixia" 74.19% (23/31). "Binneixia" showed echo enhancement at the attachment site of the medial inferior edge of the patella, and the needle point was selected 2 cm adjacent to the medial lower edge of the patella, the needle body was 45° inward, vertically thrust into the skin, with a depth of (4.13±0.27) cm. "Binneixia" enhanced the echo at the lower edge of the patella in the medial patella support belt, 2 cm of the medial lower edge of the patella is selected as the injection point, the needle body is medially 45°, vertically pierced with the skin, and the injection depth is (4.13±0.27) cm; "Hedingci" thickened the quadriceps tendon at the patellar attachment, enhanced echo, suprapatellar capsule fluid and synovial thickening, 1 cm at the upper edge of the patella is selected as the needle injection point, the patellar capsule is 45° to the head, and the needle injection depth is (2.16±0.21) cm; "Yinlingshang" echoes echo at the attachment of the tibial condyle of the goose foot tendon, selects 3 cm from the lower edge of the patella, 2 cm down for the injection point, the injection Angle is the head of the needle is 45°, and the injection depth is (1.97±0.18) cm; "Binwaixia" enhanced the echo at the attachment of the outer lower edge of the patella in the lateral patella. At 2 cm of the lateral lower edge of the patella was selected as the needle injection point, the needle body was tilted outward 45°, vertically pierced to the skin, and the needle injection depth was (4.78±0.12) cm. The clinical effective rate of the conventional treatment group was 86.21% (25/29), and the ultrasound needle knife group had a clinical effectiveness rate of 100.00% (31/31) (P<0.05). Eight patients in the conventional treatment group had minor adverse reactions, and only one patient in the ultrasound needle knife group had minor adverse reactions, indicating a higher clinical treatment safety.ConclusionUltrasound-guided visualization of needle knife treatment combined with quadriceps rehabilitation training can accurately release the focal points of the meridian tendons, stabilize the function of the knee joint, and improve the safety and effectiveness of the treatment, which is worthy of promotion.